PENDEKATAN RADIOLOGIS PADA KASUS MALROTASI INTESTINAL DENGAN MIDGUT VOLVULUS - Mulia Rahmansyah; Dyani Pitra Velyani; Gupita Nareswari; Partogi Napitupulu; Revalita Wahab; Astien Astien; Tandy Chintya Tanaji; Pramesti Indri Miranti (Jurnal Akta Trimedika, 2024)
Midgut volvulus is a condition in which the intestine has become twisted as a result of malrotation of the intestine during fetal development. It cause of an acute abdomen in neonates and important entity to be diagnosed urgently. Midgut volvulus may lead to small intestinal ischemia and gangrene. The correct diagnosis depends on both high clinical suspicion and the radiologist’s ability to recognize the specific signs of malrotation and the normal variants that can lead to the wrong diagnosis. Radiological examination; such as abdominal x-ray, ultrasound and colon in loop play an important role in the diagnosis of volvulus . A color Doppler ultrasound examination may reveal a whirlpool sign, a colon in loop (CIL) examination may show an aberrant intestinal rotation, and a plain abdominal xray may show a double bubble sign due to midgut volvulus